Optimization of the Application of the Police Application System (PAS) by the Central Integrated Police Service (SPKT) in Receiving Crime and Violation Reports at Cianjur Police Station (Advances in Police Science Research Journal, 2024)
Many crimes that occur in the Cianjur Police jurisdiction, but also many of them are not reported by citizens, so that encourage cianjur police stations to innovate by making an e-report , with the corelations by the Technology, cianjur police station make an application conducted by SPKT that work as monitoring applications. The applications name is Cianjur Police Application System (PAS). This application was made as an activities for the sake of police duties and an achievement maintainers of Security and Order in Cianjur district area, this application can be downloaded using an android smartphone on playstore .the use of the application works by responding a reports from citizens by using an e-report from the smartphone. In analyzing, the author uses several theories and concepts including Information Technology Theory, Communication Theory, Management Theory, Police Science Concepts, Excellent Service Concepts, SPKT Concepts, Concept Of Prevention and Optimization Concepts. By using a qualitative approach that is descriptive analytic, this is done in order to obtain the broadest picture of the problems that occur. The qualitative approach provides descriptive data wich form by words that delivered by the primary source at the time of the interview, thus explaining the problem in depth. The results of the study found that: (1) there were still many reports of crime and violations that were not reported by the public; (2) the role and function of the SPKT to receive reports using Technology still has a participatory and less functional role; (3) The influencing factors are internal and external. Internal, such as human resources, budget, facilities and infrastructure and leadership policies. Externals such as community participation, cooperation, and social communication. From the results of the study the authors provide advice to the Cianjur District Police SPKT to use the media in communication such as brochures and outreach. As for the advice to the Cianjur Police Chief to add Cianjur Police SPKT personnel, to take vocational education and to Master Computer Science, to procure Computers for Servers and to consider the policies of the leadership.
Keywords: Kata Kunci : Optimalisasi, Aplikasi PAS(Police Application System), Menerima Laporan, Kejahatan, Pelanggaran, dan SPKT